The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pcbi.1007941
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic bias in influenza surveillance

Abstract: Individuals in low socioeconomic brackets are considered at-risk for developing influenzarelated complications and often exhibit higher than average influenza-related hospitalization rates. This disparity has been attributed to various factors, including restricted access to preventative and therapeutic health care, limited sick leave, and household structure. Adequate influenza surveillance in these at-risk populations is a critical precursor to accurate risk assessments and effective intervention. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…While this negative association may be the result of lower exposure in impoverished areas (as suggested by [ 18 ]), it is likely that there exist spatial and social heterogeneities in surveillance caused by healthcare utilization. Indeed, Scarpino et al have shown that the most impoverished areas are blindspots in the US influenza sentinel surveillance system, ILINet, and models based on these data make the best predictions in affluent areas, while making the worst predictions in impoverished locations [ 32 ]. To better understand and respond to influenza epidemics and pandemics, we must improve our capability to detect and monitor outbreaks in at-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…While this negative association may be the result of lower exposure in impoverished areas (as suggested by [ 18 ]), it is likely that there exist spatial and social heterogeneities in surveillance caused by healthcare utilization. Indeed, Scarpino et al have shown that the most impoverished areas are blindspots in the US influenza sentinel surveillance system, ILINet, and models based on these data make the best predictions in affluent areas, while making the worst predictions in impoverished locations [ 32 ]. To better understand and respond to influenza epidemics and pandemics, we must improve our capability to detect and monitor outbreaks in at-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic health, being particularly emphasized in our study, is not the only disadvantage in the low socio-economic brackets of our society. Influenza-related complications and hospitalization rates [89] have demonstrated that preventative and therapeutic health care, limited sick leave, and household structure might also play a role that needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study of people receiving care through the U.S. Department of Veterans Affairs, Black and Hispanic patients had both higher rates of testing and higher rates of positivity (37). Disparity in surveillance quality across socioeconomic strata, where communities that experience disproportionate risk also have the poorest quality surveillance, is hardly unique to COVID-19 (38).…”
Section: Discussionmentioning
confidence: 99%